How Emotional Branding Builds Student Loyalty: Insights from Lovemarks in Indonesian Universities - Rimadewi, Anantasha Titisania (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2025)
The increasing competition among higher education institutions in Indonesia has intensified the need for strong educational branding strategies that go beyond functional and academic quality. This study examines the applicability of the lovemarks concept in the context of educational brands by investigating how its three core dimensions mystery, sensory, and intimacy influence brand love and, subsequently, student loyalty and word-of-mouth intention. Using a quantitative cross-sectional survey of undergraduate students from public and private universities in Indonesia (N ≈ 400), data were analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The findings are expected to demonstrate that all three lovemarks dimensions positively affect brand love, which in turn significantly enhances student loyalty and positive word-of-mouth. Brand love is also expected to mediate the relationship between lovemarks and behavioral outcomes. This study contributes to branding literature by extending the lovemarks framework to the education sector and provides practical insights for educational brand managers seeking to foster long-term emotional bonds with students.